THE ROLE OF BREATHING TECHNIQUES IN THE CORRECT SINGING OF A SINGER - Eminov Nurillo (Galaxy International Interdisciplinary Research Journal, 2022)
This article describes the role of breathing techniques in a singer’s proper singing. There is a lot of talk about the types of breathing in singing, breathing methods, difficulties, and the importance of proper breathing in singing. Proper breathing and its forms are very important in the art of singing. This article provides information on this.